Acceptance of C015 Eggplant (Solanum melongena L.) Variety in the Colombian Caribbean Region: measuring adoption - MARTINEZ REINA, Antonio Maria; Tordecilla Zumaqué, Lilibeth; Grandett Martínez, Liliana María; Rodríguez Pinto, María del Valle (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This work aims to contribute to the knowledge about the state of acceptance of C015 Eggplant variety, generated by Agrosavia in 2011, under the participatory plant breeding approach with farmers, who selected the material for high yields, the largest number of fruits per plant and lilac color. A study was carried out with 27 farmers selected by the random sampling method in the departments of Córdoba and Sucre of the Caribbean Region of Colombia to whom a survey was applied during 2018. Data were analyzed in the SPSS program with descriptive statistics, measures of central tendency, among which are the average, the median, maximum and minimum values, as well as the contingency table technique. The results showed that on average farmers have been growing eggplants for 11 years and only 30% had knowledge of the C015 variety, but it did not sow it; 34% of those surveyed found out about the existence of the variety through a neighbor. Similarly, 62% affirm that the decisions to plant the variety are made directly by the farmer. It is concluded that the adoption has not been successful, with a tendency to not re-sow (77%) after 5 years of release; the remaining 23% condition the sowing of this material to the availability of certified seed. The declines in acceptance are attributed to demand problems due to a lack of attributes such as shape, size and color.